-(-8x+4)+9x=

Simple and best practice solution for -(-8x+4)+9x= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(-8x+4)+9x= equation:


Simplifying
-1(-8x + 4) + 9x = 0

Reorder the terms:
-1(4 + -8x) + 9x = 0
(4 * -1 + -8x * -1) + 9x = 0
(-4 + 8x) + 9x = 0

Combine like terms: 8x + 9x = 17x
-4 + 17x = 0

Solving
-4 + 17x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4' to each side of the equation.
-4 + 4 + 17x = 0 + 4

Combine like terms: -4 + 4 = 0
0 + 17x = 0 + 4
17x = 0 + 4

Combine like terms: 0 + 4 = 4
17x = 4

Divide each side by '17'.
x = 0.2352941176

Simplifying
x = 0.2352941176

See similar equations:

| -25=5(y-4) | | 4h-6=10n | | -12m-8=70 | | 0.16666666666(12-6x)=5(x+4) | | 0.33333333333(6y-9)=-2y+13 | | 80=2(n+6) | | -3.3=4.7-4y | | 6/(2a) | | .30=x(.14)+(1-x)(.05) | | 4x-11=15-9x | | -10500x^3+5000=0 | | 6+5z=8+5z | | 102x^2+6y^2+89y-322=0 | | 55x-39x+12=-64 | | -4=-2(5n-2)-8(-7n+1) | | 28-2x=3x+18 | | .03=.14x+.05-05x | | 8+.09m=90 | | G(2)=5-7+2 | | b/0.8=12.6 | | -6m-13=74 | | 6x^2-54x/x-9•7x/6x | | -7.1=2.9-5y | | 10=1.25*p | | g/3.2=4.7 | | g/2=0.5 | | 4r^2=34-10r | | 4(24)=4(20)+4(4) | | (5x+7)+(4x-18)+(3x+2)=x | | 4q+8q+7q-7= | | 9x+x=79 | | 2(6k-7)+6(-3k+1)=22 |

Equations solver categories